KEDUDUKAN ANAK KANDUNG SEBAGAI SAKSI PERCERAIAN ORANG TUA DALAM PRAKTIK PERADILAN AGAMA DI INDONESIA - NIM. A1012221045, BOBBY YUAN IRWANTO (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT This study aims to determine and analyze the legal provisions for witnesses of biological children in parental divorce in the practice of religious courts in Indonesia and the position of biological children as witnesses of parental divorce in the practice of religious courts in Indonesia. Testimony is a certainty given to the judge in court about the disputed events by means of verbal and personal notification by a person who is not a party to the case, who is summoned to the court. The position of biological children as witnesses in divorce cases in the practice of religious courts in Indonesia is a matter that needs to be studied further in this study. The results of the study indicate that the use of biological children as witnesses in divorce cases is permitted if there is a syiqaq situation. By considering the principle of Lex Specialis Derogat Legi Generalis, biological children can be family witnesses in court, as regulated in Article 76 of the Religious Courts Law. Although judges are free to include or not this law in their considerations, it is recommended to still consider biological children as witnesses to keep up with legal developments and have broad insight. The application of this law is considered relevant in resolving divorce cases in Religious Courts and is an important guideline in determining fair and just legal decisions, especially when involving biological children. The legal implications of using biological child witnesses in divorce proceedings in Indonesia are divided into two categories: negative and positive. Negative legal implications include violations of witness rights and the principle of a fair trial, a lack of impartiality, and psychological impacts on children. Positive legal implications include protection for child witnesses, consistency of testimony, and a reduction in witness stress levels. Keywords: Biological Child, Witness, Divorce ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis ketentuan hukum saksi anak kandung perceraian orang tua dalam praktik peradilan agama di Indonesia dan kedudukan anak kandung sebagai saksi perceraian orang tua dalam praktik peradilan agama di Indonesia. Kesaksian adalah kepastian yang diberikan kepada hakim dipersidangan tentang peristiwa yang dipersengketakan dengan jalan pemberitahuan secara lisan dan pribadi oleh orang yang bukan salah satu pihak dalam perkara, yang dipanggil dipersidangan. Kedudukan anak kandung sebagai saksi dalam perkara perceraian dalam praktik peradilan agama di Indonesia merupakan hal yang perlu dikaji lebih lanjut dalam penelitian ini. Hasil penelitian yang dicapai menunjukkan bahwa Penggunaan anak kandung sebagai saksi dalam perkara perceraian diperbolehkan jika terdapat situasi syiqaq. Dengan mempertimbangkan asas Lex Specialis Derogat Legi Generalis, anak kandung dapat menjadi saksi keluarga dalam persidangan, sebagaimana yang telah diatur dalam Pasal 76 UU Peradilan Agama. Meskipun hakim bebas memasukkan atau tidak UU ini dalam pertimbangannya, disarankan agar tetap mempertimbangkan anak kandung sebagai saksi agar mengikuti perkembangan hukum dan memiliki wawasan yang luas. Penerapan hukum ini dianggap relevan dalam menyelesaikan perkara perceraian di Pengadilan Agama dan menjadi pedoman penting dalam menentukan keputusan hukum yang adil dan berkeadilan, terutama ketika melibatkan anak kandung. Implikasi hukum dari penggunaan saksi anak kandung perceraian orang tua dalam praktik peradilan di Indonesia terbagi menjadi dua, yaitu implikasi negatif dan positif. Implikasi hukum negatif yang ditimbulkan berupa pelanggaran hak saksi dan prinsip persidangan yang adil, tidak netral dan berdampak psikologis anak. Adapun implikasi hukum positif yang ditimbulkan berupa adanya perlindungan saksi anak dan konsistensi kesaksian dan pengurangan tingkat stres saksi. Kata Kunci : Anak Kandung, Saksi, Perceraian